Formula refining through composite blend of soya, alfalfa, and wheat flour; A vegan meat approach. Issue 5 (23rd January 2021) - Sharma, Aditi; Rawat, Kritika; Jattan, Priyanka; Kumar, Pradyuman; Tokusoglu, Ozlem; Kumar, Pankaj; Vural, Halil; Singh, Ajay
Abstract: Present project involves the formula development by way of standardization for vegan meat through Central Composite Rotatable Design (CCRD) of Response Surface Methodology (RSM) of Design Expert 12 (DX‐12). Soya chunks, alfalfa sprouts, and wheat flour were used as base ingredients. Preliminary experimental screening to fix the levels of these base ingredients were the basis to work ahead for formula refining through numerical optimization by way of RSM. The optimization tactics were revealed against a given set of responses viz; physico‐chemical (polyphenol, % crude protein) and sensory properties (mouthfeel and texture, color and appearance and overall acceptability) as dependent variable. Obtained product with (75.35%) soya, (1.25%) alfalfa, and (22.73%) wheat flour were evaluated for their crude protein, fiber, polyphenol, antioxidant level, water holding capacity, hardness, chewiness, and springiness as 26.13, 7.88, 0.52, 7.03, 3.962%, 1500 g, 2812 g, and 0.60 g, respectively. Practical applications: Vegan meat analogue obtained herewith is also competitive in its sensory preferences in alongwith embedded high protein, elevated fiber and antioxidant potential features too. Fortified alfalfa seeds boost it with meaty flavor thus proven to be competitive among commercial demand. Least fat utilization put it in another healthier trait owe to be a better option for obese and calorie conscious patients. Thus in nutshell, stated combination was ideal in terms of textural and sensory attributes as meat mimic.